Codisposição de lodo de esgoto sanitário e resíduos sólidos vegetai - Silva, André Gustavo da (2007)
Sanitary sewage sludge constitutes the principal subproduct of the sludge treatment process. The codisposition of organic waste presents as interesting alternative for correct destination and use of this waste. The present work was aimed to evaluate the efficiency of the process of codisposition of sanitary sewage sludge (SSS) and vegetable solid waste (VSW); to produce a seasoned compost, with good agronomic and sanitary qualities; to realize physical, chemical and biological characterization of the SSS and VSW, and to evaluate importance of the temperature in the processes of biostabilization and sanitation of the codisposed substrate. The experimental system was of completely random type with three treatments and three repetitions, consisting of nine aerobic reactors. The substrate utilized for codisposition was formed by SSS and VSW, in the following proportions: Treatment 1: 100% VSW; Treatment 2: 5% SSS + 95% VSW; Treatment 3: 10% SSS + 95% VSW. The treatments 1, 2 and 3 initially received 32.0 kg; 33.8 kg and 35.6 kg of this substrate, respectively. The weekly monitored parameters were: pH, moisture content, total volatile solids, C/N ratio and feasible eggs of helmint, besides the daily monitoring of the temperature. The temperatures attained the hemophilic range since the first day, maintaining at this level until the 5th day of the process, when started to decrease passing for the mesophilic range, staying for two more weeks till it approached to the atmospheric temperature by the end of the process. A decrease in the C/N ratio was quite low, may be due to the initial values being lower than the ideal levels. The average reduction of the total volatile solid mass in the codisposed mass during the 105 days of codisposition was 31.10%, 46.41%, 44.76%, in the 1, 2 and 3 treatments, respectively. The reduction of the helmint eggs attained an efficiency of 100% in all the treatments. Probably, the pH level, the increase in temperature and the ecological relations presents in the systems were principally responsible for the sanitation and seasoning of the produced compost, so that, the codisposition showed to be a feasible alternative for disinfection and stabilization of both the types of the solid wastes, favoring the production of a compost with environmental and sanitary conditions for utilizing in agriculture.